2016
DOI: 10.1136/jclinpath-2015-203320
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib reduces bone marrow fibrosis and overwhelms the adverse prognostic impact of reticulin formation in patients with chronic myeloid leukaemia

Abstract: According to our findings, MF regresses with imatinib therapy over time, and the MF grades at diagnosis do not have a negative impact on the responses to imatinib treatment. Therefore, the adverse prognostic impact of the MF among patients with CML seems to disappear in the era of the TKIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…BM fibrosis at diagnosis has been shown to revert in the majority of patients upon TKI treatment (Buesche et al, 2007;Eliacik et al, 2015;Narang et al, 2017) and we likewise observed this in patient 11. Tanrikulu Simsek et al (2016) furthermore confirmed a decrease in fibrosis grades after long-time imatinib treatment. It has to be noted that in a few single patients imatinib treatment was associated with induction of BM fibrosis (Buesche et al, 2007;Shanmuganathan et al, 2019) and interestingly, in patient 3 of our cohort we see development of low-grade fibrosis after 5.5 years of imatinib treatment.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…BM fibrosis at diagnosis has been shown to revert in the majority of patients upon TKI treatment (Buesche et al, 2007;Eliacik et al, 2015;Narang et al, 2017) and we likewise observed this in patient 11. Tanrikulu Simsek et al (2016) furthermore confirmed a decrease in fibrosis grades after long-time imatinib treatment. It has to be noted that in a few single patients imatinib treatment was associated with induction of BM fibrosis (Buesche et al, 2007;Shanmuganathan et al, 2019) and interestingly, in patient 3 of our cohort we see development of low-grade fibrosis after 5.5 years of imatinib treatment.…”
Section: Discussionmentioning
confidence: 64%
“…First, we could observe that in our cohort around 40% of the patients presented with MF at diagnosis and MF grade 2 correlated with higher blast counts in the blood and BM. Although the impact of BM fibrosis on prognosis was considered adverse in the pre-TKI era ( Lazzarino et al, 1986 ; Kvasnicka et al, 2001 ; Buesche et al, 2003 ), it seems to be less relevant nowadays, due to the enormous success of TKIs and the drastic improvements in patient management that were introduced ( Kantarjian et al, 2005 ; Tanrikulu Simsek et al, 2016 ). BM fibrosis at diagnosis has been shown to revert in the majority of patients upon TKI treatment ( Buesche et al, 2007 ; Eliacik et al, 2015 ; Narang et al, 2017 ) and we likewise observed this in patient 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation